Increase of Bio-Gas Power Potential - V. A. Sednin; О. F. Kraetskaya; I. N. Prokoрenia (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2012)
The paper presents a review of industrial technologies for obtaining gas-synthesis which is applicable for bio-gas enrichment process. Comparative characteristics are given in the paper. The paper thoroughly considers a technology of dry methane conversion as the most expedient variant recommended for the application in this case. The bio-gas enrichment carried out during its production expands possibilities and efficiency of its application.